KEWENANGAN PRESIDEN DALAM MEMBENTUK KABINET MENTERI MENURUT UNDANG-UNDANG NRI TAHUN 1945 DAN UNDANG-UNDANG NO. 38 TAHUN 2008 TENTANG KEMENTERIAN NEGARA - Ardiansyah, Khairi; Azeri, Septrian (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Constitutionally Indonesia adheres to a presidential system of government, in the formation of the composition of the cabinet of ministers owned by the President as a proregative right. Currently the democratic system of government that is built is not stable, this is not running the triapolitica system or checks and balances. The formulation of the constitutionally mandated presidential system turned out to be difficult to implement It is not even effective, especially supported by the weak performance and institutions of the President in maintaining political stability. Thus, it is necessary to design an effective presidential system of government with realignment both institutionally and non-institutionally.